ANALISIS FRAMING PEMBERITAAN KERETA CEPAT JAKARTA-BANDUNG DALAM DETIK.COM DAN TRIBUNNEWS.COM - Wulandari, Meysinta (Reputasi : Jurnal Public Relations, 2024)
The government has chosen high-speed trains as a form of modernizing mass transportation to build connectivity between cities, provinces, and regions Despite being seen as a solution to various issues, the launch of the high-speed train has sparked controversy and generated extensive media coverage Media, as a means of communication, plays a crucial role in influencing the public The focus of this research is how the media frames news related to the Jakarta-Bandung highspeed train in the online news media detik.com and tribunnews.com. The objective to be achieved in this study is to determine the news framing carried out by the online media detik.com and tribunnews.com related to the news about the JakartaBandung high-speed train. This research utilizes Entman's framing model analysis, consisting of four components: (1) defining the problem, (2) identifying the causes of the problem, (3) offering solutions to address the issue, and (4) making moral judgments regarding the matter The results of the research found that Detik.com and Tribunnews.com have different approaches. Detik.com emphasizes the technical and financial aspects of the project with a constructive tone, presenting information in a structured manner and supporting improvement efforts. In contrast, Tribunnews.com focuses on controversy, in-depth criticism, and emphasizes the need for transparency and regulatory compliance.